How do tree- and stand-level factors influence belowground biomass and carbon storage in tanoak (Notholithocarpus densiflorus)? - Brandon H. Namm; John-Pascal Berrill (The Forestry Chronicle, 2020)
Tanoak (Notholithocarpus densiflorus) is the most common hardwood in northern California forests, yet its capacity for belowground carbon storage is unknown. To study relationships between coarse roots and tree and stand variables, we destructively sampled twelve tanoak root systems in Humboldt County, California. To estimate belowground biomass, we summed measured biomass of the root ball and a subsample of lateral roots along with predicted biomass of unmeasured coarse roots. Tree size was the best linear predictor of belowground biomass and carbon, indicating that a 25-cm diameter tanoak, for example, stored 70 kg of biomass and 34 kg of carbon in its root system. Stand density was also influential: a doubling of stand density index reduced belowground carbon by 22% for the average tanoak. The mean root-toshoot ratio of 0.35 varied between 0.11 and 0.65, with larger tanoak at high stand densities allocating proportionally less biomass belowground than small open-grown tanoak. The findings highlight the importance of accounting for stand density effects, otherwise belowground carbon will be under predicted in low-density stands managed for tree health, vigor, and resistance to drought and wildfire, or overestimated in forests managed at high densities for high carbon sequestration.